2007
DOI: 10.1021/es0709977
|View full text |Cite
|
Sign up to set email alerts
|

Bioconcentration Factor Hydrophobicity Cutoff:  An Artificial Phenomenon Reconstructed

Abstract: The debate on whether highly hydrophobic organic chemicals (with log Kow > 5-6) bioconcentrate less than may be expected from their hydrophobicity is still not settled. The often-observed hydrophobicity "cutoff" might either be explained by artifacts occurring during bioconcentration factor (BCF) measurements or by a true mechanism, i.e., reduced uptake of larger molecules due to decreased membrane permeation. In this paper, we advocate there is no hydrophobicity cutoff, at least not for compounds with log Kow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
158
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(175 citation statements)
references
References 33 publications
14
158
3
Order By: Relevance
“…Numerous studies have shown that the bioconcentration of POPs can be described by the octanol-water partition coefficients (K ow ). However, for highly hydrophobic POPs with log K ow values greater than 5.5-6, the picture is not so clear (Jonker and van der Heijden, 2007). In the present study, logarithmic average of bioconcentration factors increased with log K ow reaching about 5, and then decreased in the marine fish (Fig.…”
Section: Dongjiangcontrasting
confidence: 69%
See 1 more Smart Citation
“…Numerous studies have shown that the bioconcentration of POPs can be described by the octanol-water partition coefficients (K ow ). However, for highly hydrophobic POPs with log K ow values greater than 5.5-6, the picture is not so clear (Jonker and van der Heijden, 2007). In the present study, logarithmic average of bioconcentration factors increased with log K ow reaching about 5, and then decreased in the marine fish (Fig.…”
Section: Dongjiangcontrasting
confidence: 69%
“…(2) In this study, solvent extractions result in higher C w for PAHs having a log K ow > 5.5. Overestimated aqueous concentrations can cause the typical drop in log BCF-log K ow curves at higher hydrophobicity (Jonker and van der Heijden, 2007).…”
Section: Dongjiangmentioning
confidence: 99%
“…This curvilinearity was attributed to the difference in the Gibbs free energies for cavity formation in PDMS and octanol that can become significant for larger molecules [18]. Jonker and van der Heijden [22] instead ascribed the curvilinearity, or hydrophobicity cutoff in their term, to insufficient time to equilibrium and the presence of a third phase, but their conclusion of no hydrophobicity cutoff was only applicable to compounds with log K OW up to 7.5. In the present study, 23 target BDE congeners with log K OW spanning from 4.34 to 9.87, among which nine congeners have log K OW greater than 8, were selected for the kinetic experiments.…”
Section: Sorption Kinetics Of Target Bde Congenersmentioning
confidence: 99%
“…The BCFs of untransformed chemicals measured in unfed fish (i.e., no chemical uptake from the diet and no fecal egestion) are thus expected to be greater than those in fish that are fed uncontaminated food (i.e., no chemical uptake but fecal egestion occurs). Ambiguity can occur between the truly dissolved and total concentration in water [12,13], but here we assume the former to apply. Reaching a true steady state or equilibrium may not always be feasible experimentally, but this can be circumvented by measuring the uptake rate constant from water (k 1 ) and the clearance rate constant from the organism (k 2 ) and calculating the BCF as k 1 /k 2 .…”
Section: Bioaccumulation Metricsmentioning
confidence: 99%
“…As noted earlier, the ratio k D /k R is relatively independent of K OW , but when log K OW exceeds a value of 7, this ratio decreases because of the decrease in the food assimilation efficiency caused by the increasing water phase resistance (i.e., the low internal water phase concentration), which retards transport from the gastrointestinal tract to the blood. An additional separate issue is the increased partitioning to particulate matter that reduces the dissolved concentration in the water [12,13]. Equation 8 shows that BMF 21 is controlled by the ratio of BCFs, which is mainly determined by the relative lipid contents of predator and prey, and more importantly by the ratio of the equilibrium multipliers M 2 /M 1 that characterize the respective departures from equilibrium.…”
Section: Mathematical Relationships Among Bioaccumulation Metrics In mentioning
confidence: 99%